Preparation method of alkaline polyionic liquid catalyst and its application in catalyzing the synthesis of dimethyl carbonate from ethylene carbonate

By polymerizing imidazole ionic liquids and N-containing alkaline groups in ionic liquid catalysts, an efficient alkaline polyion liquid catalyst is designed, which solves the problems of large viscosity and difficult recovery of existing ionic liquid catalysts, and achieves high efficiency Catalytic and economical catalyst regeneration.

CN116178626BActive Publication Date: 2024-12-13FUJIAN ZHONGSHENG HONGYE NEW MATERIAL TECH CO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310056394.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-17
Publication Date
2024-12-13
Estimated Expiration
2043-01-17

AI Technical Summary

Technical Problem

The existing ionic liquid catalyst has a high viscosity and is difficult to recover after the reaction is completed, which limits its application in actual production.

Method used

Imidazole ionic liquids are used as cationic frameworks, and doped with N-containing alkaline groups for radical polymerization. Anion exchange is designed to design an efficient alkaline polyion liquid catalyst for catalyzing the reaction of vinyl carbonate and methanol to form dimethyl carbonate. ester.

Benefits of technology

The catalyst is achieved with excellent high swelling and catalytic activity, and the catalyst can be separated and regenerated by simple centrifugation and vacuum freeze-drying, saving operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116178626B_ABST
    Figure CN116178626B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an alkaline polyionic liquid catalyst and its application in the process of catalyzing the synthesis of dimethyl carbonate from ethylene carbonate. The catalyst of the invention uses an imidazole ionic liquid as a cationic skeleton, is doped with a monomer containing a basic group of N, and is subjected to free radical polymerization to obtain a solid-state stable polyionic liquid, and then anion exchange is performed to design and prepare a series of alkaline polyionic liquids containing different anions. This method uses an imidazole ionic liquid as a cationic skeleton, is polymerized with ionic liquid monomers containing different basic functional groups, and then different anions are exchanged, thereby significantly changing the alkalinity and swelling property of the polyionic liquid. This makes the catalyst have the advantages of ultra-high swelling rate, rich basic sites, easy recovery and separation, etc. The catalyst is applied to the transesterification reaction of ethylene carbonate and methanol to generate dimethyl carbonate, and has excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic material synthesis, and in particular to a method for preparing a series of alkaline polyionic liquids containing different anions, which is designed by using an imidazole ionic liquid as a cationic skeleton, doping a monomer containing a basic group of N, performing free radical polymerization, and obtaining a solid stable polyionic liquid, and then performing anion exchange, and applying the same. Background Art

[0002] Dimethyl carbonate (DMC), as the simplest dialkyl carbonate, has unique physical and chemical properties. Based on its high oxygen content (53.28%) and relatively high carbon-hydrogen ratio, low boiling point that is conducive to mixing and spray atomization, complete solubility with fossil fuels (diesel and gasoline), and easy decomposition to form methoxyformyl (CH3OC=O) to reduce the formation of carbon smoke, it can be used as an environmentally friendly fuel additive. In the field of electrochemistry, due to its low viscosity and excellent solubility in lithium salts, it is beneficial to reduce electrolyte resistance, thereby improving electrolyte conductivity, and can be used as an electrolyte solvent for lithium-ion batteries. In the field of organic synthesis, based on the characteristic that DMC molecular structure contains active groups such as carbonyl (C=O), methyl (-CH3), methoxy (CH3O-), etc., it can replace toxic and corrosive methylation or carbonylation reagents such as phosgene and dimethyl sulfate for methylation, carbonylation, methoxylation and ester exchange reactions, and related organic synthesis reactions in the fields of medicine and pesticides. It is an important green chemical intermediate and conforms to the current green, environmentally friendly and sustainable development of chemical production concepts.

[0003] At present, the process of catalyzing the reaction of ethylene carbonate (EC) and methanol (MeOH) with traditional alkaline catalysts (sodium methoxide, NaOH, etc.) at home and abroad is very mature. The catalyst production cost is low and the selectivity and product yield are high. However, this catalyst has the disadvantages of severe equipment corrosion and high waste generation. Although heterogeneous catalysts (molecular sieves, montmorillonite, metal oxides, etc.) simplify the process and solve the problem of equipment corrosion, they all have some other problems to varying degrees, such as: large mass transfer resistance, pipeline blockage, complex preparation, harsh reaction conditions, too high alcohol-alkane ratio, uneven product distribution, poor catalyst stability, etc. In contrast, alkaline ionic liquids are easy to prepare, require mild reaction conditions, do not require other solvents, and the catalytic activity can remain stable after multiple cycles of catalysis. However, the viscosity of ionic liquids is relatively large, and it is difficult to recover after the reaction, which limits their application in actual production.

[0004] Polyionic liquids refer to a type of ionic liquid polymers that are generated by the polymerization of ionic liquid monomers and have anionic and cationic groups on the repeating units, which overcomes the limitations of the thermodynamic properties of ionic liquids themselves. They are widely used in the field of catalysis because they have both the structural adjustability of ionic liquids, chemical / thermal stability, and mechanical stability of polymers. Summary of the invention

[0005] The purpose of the present invention is to provide an alkaline polyionic liquid catalyst for catalyzing the reaction of ethylene carbonate and methanol to produce dimethyl carbonate and a preparation method thereof, so as to overcome the problems of the existing ionic liquid catalysts such as high viscosity and difficulty in recovery after the reaction. Due to its high swelling property, the catalytic activity is excellent, which is equivalent to that of homogeneous catalysts.

[0006] The present invention adopts the following technical solutions:

[0007] A method for preparing an alkaline polyionic liquid: using an imidazole ionic liquid as a cationic skeleton, doping a monomer containing a basic group of N, performing free radical polymerization, and then exchanging anionic groups with a certain alkalinity to obtain an alkaline polyionic liquid that efficiently catalyzes the reaction of ethylene carbonate and methanol to generate dimethyl carbonate.

[0008] The specific steps include:

[0009] (1) Preparation of ionic liquid monomer DC-VIM: 1,4-dichlorobenzyl was dissolved in acetonitrile and placed in a Schlenk reaction tube. A magnetic stirrer was added and 1-vinylimidazole was added dropwise into the reaction tube. The temperature was then raised to 80 °C and the reaction was continued for 24 h. After the reaction, the obtained white solid powder was washed three times with acetonitrile to remove the residual 1,4-dichlorobenzyl and 1-vinylimidazole, and vacuum dried to obtain a linker loaded with imidazole, which was recorded as DC-VIM.

[0010] (2) Ionic liquid monomer N X Preparation of -VBC: The N-containing basic group was dissolved in acetone, and after dissolution, it was placed in a Schlenk reaction tube, and a magnetic stirrer was added. 4-vinylbenzyl chloride was added dropwise into the reaction tube, and then the temperature was raised to 60 °C. After the reaction for 1 h, the reaction temperature was lowered to 30 °C and the reaction was continued for 24 h. After the reaction, the obtained white solid powder was washed three times with ice acetone to remove the residual N-containing basic group and 4-vinylbenzyl chloride, and vacuum dried to obtain a monomer with a N-containing basic group, which was recorded as N X -VBC;

[0011] (3) Polymerization reaction: DC-VIM and N X-VBC was dissolved in ethanol in a certain proportion, and then placed in a high-pressure vacuum reaction tube, and a magnetic stirring was added to make it fully dissolved. Azobisisobutyronitrile was added to the reaction tube to make it completely dissolved, and then inert gas was filled to seal it, and then the temperature was raised to 80 ° C and reacted for 24 h. After the reaction was completed, the yellow gel-like solid was washed three times with deionized water to remove the residual DC-VIM and N X -VBC, vacuum dried to obtain a polyionic liquid, denoted as [N X FPIL-Y][Cl];

[0012] (4) [N X FPIL-Y][Cl] was placed in a chromatography column, sodium hydroxide solution was added, and the liquid was allowed to drip slowly. The test was performed with a standard silver nitrate solution until the test liquid became transparent. The polyionic liquid was taken out, 200 ml of deionized water was added, and then acid was added to completely dissolve it in water. After shaking in a shaker for 24 h, the polyionic liquid was taken out and washed three times with hot deionized water to remove the residual acid. The polyionic liquid was dried in a vacuum to obtain an alkaline polyionic liquid.

[0013] Furthermore, the nitrogen-containing basic group in step (2) is one of triethylamine, triethylenediamine, and 1,8-diazabicyclo[5.4.0]undec-7-ene.

[0014] Furthermore, the polymer obtained in step (3) is a self-polymer of DC-VIM, or a polymer of DC-VIM and N X -VBC is polymerized in a molar ratio of 2:1-4:1.

[0015] Furthermore, the inert gas is one of nitrogen, argon and helium.

[0016] Furthermore, the concentration of the sodium hydroxide solution in step (4) is 1 mol / L.

[0017] Furthermore, the acid in step (4) includes one of phenol, 1,2,4-triazole, 2-hydroxypyridine, imidazole, and p-nitrophenol.

[0018] Application: The alkaline polyionic liquid is used as a catalyst in the ester exchange of catalyzing the reaction of ethylene carbonate and methanol to generate dimethyl carbonate.

[0019] Furthermore, after the catalytic reaction is completed, the catalyst is regenerated by washing three times with deionized water, filtering, and drying with a vacuum freeze dryer.

[0020] The present invention adopts the above technical solution and has the following beneficial effects:

[0021] The catalyst of the present invention uses imidazole ionic liquid as a cationic skeleton, doped with monomers containing N-containing basic groups, and subjected to free radical polymerization to obtain a solid-state stable polyionic liquid, and then anion exchange is performed to design and prepare a series of basic polyionic liquids containing different anions. N doping increases the basic active sites and also exhibits extremely high swelling properties, which is conducive to the rapid diffusion of reactants inside the catalyst. It has the advantages of abundant basic sites, easy recovery and separation, and excellent catalytic performance.

[0022] The alkaline polyionic liquid involved in the invention is used to catalyze the transesterification reaction of ethylene carbonate and methanol to produce dimethyl carbonate, with excellent yield, and the catalyst can be separated by simple centrifugation and the catalyst can be regenerated by vacuum freeze drying, which effectively saves operating costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) is the structure of DC-VIM, and (b) is the NMR spectrum of DC-VIM;

[0024] Figure 2 (a) The structure of N1-VBC, (b) The NMR spectrum of N1-VBC;

[0025] Figure 3 The FT-IR spectrum of the polyionic liquid with imidazole ionic liquid as the cationic skeleton and doped with nitrogen-containing basic groups;

[0026] Figure 4 (a) is a diagram showing the catalytic performance of the alkaline polyionic liquids prepared in Examples 1-4; (b) is a diagram showing the catalytic performance of the alkaline polyionic liquids prepared in Examples 5-7;

[0027] Figure 5 This is the physical adsorption diagram of a polyionic liquid with imidazolium ionic liquid as the cationic skeleton and doped with nitrogen-containing basic groups. Specific implementation methods

[0028] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments. Example 1

[0029] (1) 5.0794 g of 1,4-dichlorobenzyl was dissolved in 100 mL of acetonitrile and placed in a Schlenk reaction tube. A magnetic stirrer was added and 5.4735 g of 1-vinylimidazole was added dropwise into the reaction tube. The temperature was then raised to 80 °C and the reaction was continued for 24 h. After the reaction, the obtained white solid powder was washed three times with acetonitrile to remove the residual 1,4-dichlorobenzyl and 1-vinylimidazole, and then dried in vacuum to obtain a linker loaded with imidazole, which was recorded as DC-VIM.

[0030] The structure of DC-VIM is as follows Figure 1 As shown in (a), Figure 1 (b) is the NMR characterization of DC-VIM monomer: 1H NMR (600MHz, MeOD) δ 8.08 (d, J = 2.2 Hz, 2H, CH), 7.79 (d, J = 2.2 Hz, 2H, CH), 7.61(s, 4H, Ar-H), 7.31 (dd, J = 15.6, 8.7 Hz, 2H, CH), 5.97 (dd, J = 15.6, 2.8Hz, 2H, CH), 5.56 (s, 4H, CH2), 5.48 (dd, J = 8.7, 2.8 Hz, 2H, CH).

[0031] Theoretically, there should be no deuterated water in the spectrum, or the integral of the deuterated water part should be much smaller than that of deuterated methanol. However, in fact, the integral area of ​​the deuterated water part is larger than that of deuterated methanol. This is because the hydrogen displacement at the H position of the compound DC-VIM overlaps with the deuterated water displacement, indicating that the DC-VIM monomer has been successfully synthesized.

[0032] (2) Dissolve 5 mL of triethylamine in acetone, place in a Schlenk reaction tube, add a magnetic stirrer, add 5 mL of 4-vinylbenzyl chloride dropwise into the reaction tube, then raise the temperature to 60 °C, react for 1 h, then lower the reaction temperature to 30 °C and react for 24 h. After the reaction, wash the obtained white solid powder three times with ice acetone to remove residual triethylamine and 4-vinylbenzyl chloride, and dry in vacuo to obtain a monomer loaded with triethylamine, which is denoted as N1-VBC.

[0033] The structure of N1-VBC is as follows Figure 2 As shown in (a), Figure 2(b) is the NMR characterization of N1-VBC monomer: 1H NMR (600MHz, D2O) δ 7.51 (d, J = 8.2 Hz, 2H, Ar-H), 7.41 (d, J = 8.2 Hz, 2H, Ar-H),6.74 (dd, J = 17.7, 11.0 Hz, 1H, CH), 5.85 (d, J = 17.7 Hz, 1H, CH), 5.32 (d,J = 11.0 Hz, 1H, CH), 4.31 (s, 2H, CH2), 3.14 (q, J = 7.2 Hz, 6H, 3CH2), 1.30(t, J = 7.2 Hz, 9H, 3CH3), indicating that N1-VBC monomer has been successfully synthesized.

[0034] (3) The DC-VIM and N1-VBC synthesized in step (1) and step (2) were reacted in a molar ratio of 3:1, 1.1989 g DC-VIM and 0.2792 g N1-VBC were dissolved in ethanol, placed in a high-pressure vacuum reaction tube after dissolution, and magnetic stirring was added to fully dissolve the DC-VIM and N1-VBC. 0.0758 g azobisisobutyronitrile was added to the reaction tube to completely dissolve the DC-VIM and N1-VBC. The reaction tube was sealed with nitrogen and then heated to 80 °C and reacted for 24 h. After the reaction, the yellow gel-like solid was washed three times with deionized water to remove the residual DC-VIM and N1-VBC, and dried in vacuum to obtain a polyionic liquid, which was recorded as [N1FPIL-3][Cl].

[0035] (4) If Figure 3 The FT-IR spectrum of [N1FPIL-3][Cl] in the sample showed that -1 It is caused by the CH stretching vibration of the imidazole ring, 2700 cm -1 -2992 cm -1 The absorption peaks in the range are derived from the stretching vibration of saturated CH on methyl and methylene groups, 1557 cm -1 The vibration peak of the imidazole ring skeleton nearby, 1554 cm -1 , 1637 cm -1 The peak of the aromatic ring contraction vibration is 1071 cm -1 The absorption peak is caused by CN stretching vibration.

[0036] (5) Place [N1FPIL-3][Cl] in a chromatography column, add 1 mol / L sodium hydroxide solution, allow the liquid to drip slowly, and detect with a silver nitrate standard solution until the test liquid becomes transparent. Remove the polyionic liquid, add 200 ml of deionized water, and then add 1.5 g of phenol to completely dissolve it in water. Oscillate on a shaker for 24 h, then take it out and wash it three times with hot deionized water to remove residual acid. Then, vacuum dry it to obtain an alkaline polyionic liquid, which is recorded as [N1FPIL-3][PHO].

[0037] (6) Figure 3 The FT-IR spectrum of [N1FPIL-3][PHO] in the sample showed that -1 The absorption peak at 1266 cm is caused by CN stretching vibration. -1 The carbon-oxygen bond vibration peak of phenol is 1396 cm -1 , 1669 cm -1 The peak of the aromatic ring stretching vibration is 1599 cm -1 The vibration peak of the imidazole ring skeleton nearby. Figure 5 As shown in the physical adsorption diagram of [N1FPIL-3][PHO], the peak position of [N1FPIL-3][PHO] is 125 ℃-225 ℃, which shows that [N1FPIL-3][PHO] is a weak base with a peak area of ​​22 and the largest alkalinity.

[0038] (7) 0.011 g [N1FPIL-3][PHO] was used as a catalyst to prepare dimethyl carbonate. 0.55 g ethylene carbonate and 2.0011 g methanol were reacted at 70 °C for 10 h. After the reaction, the yield of dimethyl carbonate was detected by gas chromatography internal standard method. Figure 4 As shown in (a), the dimethyl carbonate yield of [N1FPIL-3][PHO] can reach 66% after 10 h of reaction.

[0039] Example 2

[0040] (1) The DC-VIM and N1-VBC obtained in step (1) and step (2) of Example 1 are polymerized in a molar ratio of 2:1. 0.8753 g of DC-VIM and 0.3189 g of N1-VBC are dissolved in ethanol, placed in a high-pressure vacuum reaction tube after dissolution, and magnetic stirring is added to fully dissolve the mixture. 0.0615 g of azobisisobutyronitrile is added to the reaction tube to completely dissolve the mixture. The reaction tube is then sealed with an inert gas, and the temperature is then raised to 80° C. and the reaction is carried out for 24 h. After the reaction is completed, the obtained yellow gel-like solid is washed three times with deionized water to remove the residual DC-VIM and N1-VBC, and vacuum dried to obtain a polyionic liquid, which is denoted as [N1FPIL-2][Cl]. According to the method of step (5) in Example 1, an alkaline polyionic liquid is obtained, which is denoted as [N1FPIL-2][PHO].

[0041] (2) The monomer of [N1FPIL-2][PHO] is the same as the monomer of the alkaline polyionic liquid obtained in step (5) of Example 1, so the infrared is the same and will not be repeated below. 0.011 g of [N1FPIL-2][PHO] was used as a catalyst to prepare dimethyl carbonate. 0.55 g of ethylene carbonate and 2.0011 g of methanol were reacted at 70 °C for 10 h. After the reaction, the yield of dimethyl carbonate was detected by gas chromatography internal standard method. The catalytic effect is as follows Figure 4 As shown in (a), the dimethyl carbonate yield of [N1FPIL-2][PHO] can reach 58% after 10 h of reaction. Example 3

[0042] (1) The DC-VIM and N1-VBC obtained in step (1) and step (2) of Example 1 are polymerized in a molar ratio of 4:1. 1.211 g of DC-VIM and 0.2182 g of N1-VBC are dissolved in ethanol, placed in a high-pressure vacuum reaction tube after dissolution, and magnetic stirring is added to fully dissolve the DC-VIM. 0.0738 g of azobisisobutyronitrile is added to the reaction tube to completely dissolve the DC-VIM. The reaction tube is then sealed with an inert gas, and the temperature is raised to 80° C. for reaction for 24 h. After the reaction is completed, the obtained yellow gel-like solid is washed three times with deionized water to remove the residual DC-VIM and N1-VBC, and vacuum dried to obtain a polyionic liquid, which is denoted as [N1FPIL-4][Cl]. According to the method of step (5) of Example 1, an alkaline polyionic liquid is obtained, which is denoted as [N1FPIL-4][PHO]

[0043] (2) The monomer of [N1FPIL-4][PHO] is the same as the monomer of the alkaline polyionic liquid obtained in step (5) of Example 1, so the infrared is the same and will not be repeated below. 0.011 g of [N1FPIL-4][PHO] was used as a catalyst to prepare dimethyl carbonate. 0.55 g of ethylene carbonate and 2.0011 g of methanol were reacted at 70 °C for 10 h. After the reaction, the yield of dimethyl carbonate was detected by gas chromatography internal standard method. The catalytic effect is as follows Figure 4 As shown in (a), the dimethyl carbonate yield of [N1FPIL-4][PHO] can reach 59% after 10 h of reaction. Example 4

[0044] (1) The DC-VIM obtained in step (1) of Example 1 was self-polymerized. 1.652 g of DC-VIM was dissolved in ethanol. After dissolution, it was placed in a high-pressure vacuum reaction tube and magnetic stirring was added to fully dissolve it. 0.0826 g of azobisisobutyronitrile was added to the reaction tube and completely dissolved. Then, nitrogen was filled and sealed. Then, the temperature was raised to 80°C and the reaction was reacted for 24 hours. After the reaction was completed, the obtained yellow gel-like solid was washed three times with deionized water to remove the residual DC-VIM, and vacuum dried to obtain a polyionic liquid, which was recorded as [N1FPIL-0][Cl]. According to the method of step (5) of Example 1, an alkaline polyionic liquid was obtained, which was recorded as [N1FPIL-0][PHO]

[0045] (2) If Figure 3 The FT-IR spectrum of [N1FPIL-0][PHO] in the -1 The absorption peak at 1260 cm is caused by CN stretching vibration. -1 The carbon-oxygen bond vibration peak of phenol is 1429 cm -1 -1672 cm -1 The peak of the aromatic ring contraction vibration is 2947 cm -1 is caused by the CH stretching vibration of the imidazole ring, 1580 cm -1 The vibration peak of the imidazole ring skeleton near the reaction was 0.011 g [N1FPIL-0] [PHO] was used as a catalyst to prepare dimethyl carbonate. 0.55 g ethylene carbonate and 2.0011 g methanol were reacted at 70 °C for 10 h. After the reaction, the yield of dimethyl carbonate was detected by gas chromatography internal standard method. The catalytic effect is as follows Figure 4 As shown in (a), the dimethyl carbonate yield of [N1FPIL-0][PHO] can reach 51% after 10 h of reaction. Example 5

[0046] (1) Place [N1FPIL-3][Cl] obtained in Example 1 into a chromatography column, add 1 mol / L sodium hydroxide solution, open the chromatography column, allow the liquid to drip slowly, detect with a silver nitrate standard solution until the test liquid becomes transparent, take out the polyionic liquid, add 200 ml of deionized water, and then add 1.5 g of imidazole to completely dissolve it in water. After shaking on a shaker for 24 hours, take out, wash three times with hot deionized water to remove residual acid, and vacuum dry to obtain an alkaline polyionic liquid, recorded as [N1FPIL-3][IM].

[0047] (2) If Figure 3 The FT-IR spectrum of [N1FPIL-3][IM] in the sample showed that -1 The absorption peak at 1429 cm is caused by CN stretching vibration. -1 -1672 cm -1 The peak of the aromatic ring contraction vibration is 2947 cm -1 is caused by the CH stretching vibration of the imidazole ring, 1580 cm -1 The vibration peak of the imidazole ring skeleton nearby. Figure 5 As shown in the physical adsorption diagram of [N1FPIL-3][IM], the peak area of ​​[N1FPIL-3][IM] is 8.55, and the peak position is 125 ℃-225 ℃. It can be seen that [N1FPIL-3][IM] is a weak base.

[0048] (3) 0.011 g [N1FPIL-3][IM] was used as a catalyst to prepare dimethyl carbonate. 0.55 g ethylene carbonate and 2.0011 g methanol were reacted at 70 °C for 10 h. After the reaction, the yield of dimethyl carbonate was detected by gas chromatography internal standard method. Figure 4 As shown in (b), after 10 h of reaction, the yield of dimethyl carbonate of [N1FPIL-3][IM] can reach 37.64%. Example 6

[0049] (1) [N1FPIL-3][Cl] obtained in Example 1 was placed in a chromatography column, 1 mol / L sodium hydroxide solution was added, the chromatography column was opened, the liquid was allowed to drip slowly, and a standard silver nitrate solution was used for detection until the detection liquid became transparent. The polyionic liquid was taken out, 200 ml of deionized water was added, and then 1.5 g of 2-hydroxypyridine was added to completely dissolve it in water. After shaking on a shaker for 24 h, the mixture was taken out and washed three times with hot deionized water to remove residual acid. The mixture was vacuum dried to obtain an alkaline polyionic liquid, which was recorded as [N1FPIL-3][2-PyO].

[0050] (2) If Figure 3The FT-IR spectrum of [N1FPIL-3][2-PyO] in the sample showed that -1 and 1670 cm -1 is the CH deformation vibration absorption peak on the pyridine molecular skeleton, 1389 cm -1 , 1594 cm -1 The peak of the aromatic ring contraction vibration is 1568 cm -1 The vibration peak of the imidazole ring skeleton nearby, 1078 cm -1 The absorption peak is caused by CN stretching vibration. Figure 5 As shown in the physical adsorption diagram of [N1FPIL-3][2-PyO], the peak area of ​​[N1FPIL-3][2-PyO] is 10.69, and the peak position is 125 ℃-225 ℃, which shows that [N1FPIL-3][2-PyO] is a weak base.

[0051] (3) 0.011 g [N1FPIL-3][2-PyO] was used as a catalyst to prepare dimethyl carbonate. 0.55 g ethylene carbonate and 2.0011 g methanol were reacted at 70 °C for 10 h. After the reaction, the yield of dimethyl carbonate was detected by gas chromatography internal standard method. Figure 4 As shown in (b), the dimethyl carbonate yield of [N1FPIL-3][2-PyO] can reach 51% after 10 h of reaction.

[0052] Example 7

[0053] (1) [N1FPIL-3][Cl] obtained in Example 1 was placed in a chromatography column, 1 mol / L sodium hydroxide solution was added, the chromatography column was opened, the liquid was allowed to drip slowly, and a standard silver nitrate solution was used for detection until the detection liquid became transparent. The polyionic liquid was taken out, 200 ml of deionized water was added, and then 1.5 g of 1,2,4-triazole was added to completely dissolve it in water. After shaking on a shaker for 24 h, the mixture was taken out and washed three times with hot deionized water to remove residual acid. The mixture was dried in a vacuum to obtain an alkaline polyionic liquid, which was recorded as [N1FPIL-3][Triz].

[0054] (2) If Figure 3 The FT-IR spectrum of [N1FPIL-3][Triz] in the sample showed a peak at 1375 cm -1 and 1150 cm -1 The CN and C=N stretching vibration peaks on the triazole molecular skeleton are 1439 cm -1 -1668 cm -1 The peak of the aromatic ring contraction vibration is 1576 cm -1 The vibration peak of the imidazole ring skeleton nearby, 1484 cm -1The deformation vibration absorption peak of methyl CH at 3139 cm -1 It is caused by the CH stretching vibration on the imidazole ring. Figure 5 As shown in the physical adsorption diagram of [N1FPIL-3][Triz], the peak area of ​​[N1FPIL-3][Triz] is 7.96, and the peak position is 125 ℃-225 ℃, which shows that [N1FPIL-3][Triz] is a weak base.

[0055] (3) 0.011 g [N1FPIL-3][Triz] was used as a catalyst to prepare dimethyl carbonate. 0.55 g ethylene carbonate and 2.0011 g methanol were reacted at 70 °C for 10 h. After the reaction, the yield of dimethyl carbonate was detected by gas chromatography internal standard method. Figure 4 As shown in (b), after 10 h of reaction, the yield of dimethyl carbonate of [N1FPIL-3][Triz] can reach 28.9%.

[0056] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. An application of an alkaline polyionic liquid as a catalyst in catalyzing the reaction of ethylene carbonate and methanol to produce dimethyl carbonate, characterized in that: The preparation method of the alkaline polyionic liquid comprises the following steps: (1) Preparation of ionic liquid monomer DC-VIM: 1,4-dichlorobenzyl was dissolved in acetonitrile and placed in a Schlenk reaction tube. A magnetic stirrer was added and 1-vinylimidazole was added dropwise into the reaction tube. The temperature was then raised to 80 °C and the reaction was continued for 24 h. After the reaction, the obtained white solid powder was washed three times with acetonitrile to remove the residual 1,4-dichlorobenzyl and 1-vinylimidazole, and vacuum dried to obtain a linker loaded with imidazole, which was recorded as DC-VIM. (2) Ionic liquid monomer N X Preparation of -VBC: The N-containing basic group was dissolved in acetone, and after dissolution, it was placed in a Schlenk reaction tube, and a magnetic stirrer was added. 4-vinylbenzyl chloride was added dropwise into the reaction tube, and then the temperature was raised to 60 °C. After the reaction for 1 h, the reaction temperature was lowered to 30 °C and the reaction was continued for 24 h. After the reaction, the obtained white solid powder was washed three times with ice acetone to remove the residual N-containing basic group and 4-vinylbenzyl chloride, and vacuum dried to obtain a monomer with a N-containing basic group, which was recorded as N X -VBC; (3) Polymerization reaction: DC-VIM and N X -VBC was dissolved in ethanol in a certain proportion, and then placed in a high-pressure vacuum reaction tube, and a magnetic stirring was added to make it fully dissolved. Azobisisobutyronitrile was added to the reaction tube to make it completely dissolved, and then inert gas was filled to seal it, and then the temperature was raised to 80 ° C and reacted for 24 h. After the reaction was completed, the yellow gel-like solid was washed three times with deionized water to remove the residual DC-VIM and N X -VBC, vacuum dried to obtain a polyionic liquid, denoted as [N X FPIL-Y][Cl]; (4) [N X FPIL-Y][Cl] is placed in a chromatography column, sodium hydroxide solution is added, the liquid is allowed to drip slowly, and a silver nitrate standard solution is used for detection until the detection liquid becomes transparent, the polyionic liquid is taken out, 200 ml of deionized water is added, and then one of phenol, 1,2,4-triazole, 2-hydroxypyridine, imidazole, and p-nitrophenol is added to completely dissolve it in water, and the mixture is taken out after shaking in a shaker for 24 h, washed three times with hot deionized water, and vacuum dried to obtain an alkaline polyionic liquid; The N-containing basic group is one of triethylamine, triethylenediamine, and 1,8-diazabicyclo[5.4.0]undec-7-ene; The polymer obtained in step (3) is DC-VIM and N X -VBC is polymerized in a molar ratio of 2:1-4:1; The inert gas is one of nitrogen, argon and helium; The concentration of the sodium hydroxide solution described in step (4) is 1 mol / L.

Citation Information

Patent Citations

  • High-stability alkaline solid catalytic material as well as preparation method and application thereof

    CN114700113A